2014
DOI: 10.1039/c4ra05045b
|View full text |Cite
|
Sign up to set email alerts
|

Divergent reaction: metal & oxidant free direct C–H aryloxylation and hydride free formal reductive N-benzylation of N-heterocycles

Abstract: Metal, oxidant and other additive-free novel methods for direct C–H aryloxylation of aliphatic amines are developed. Divergent reaction for the synthesis of ring-fused oxazine and arylmethylamine is developed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…All derivatives showed in vivo and in vitro anti-inammatory and anthelmintic activities against reference drugs diclofenac and albendazole. 80 Jana et al 81 reported the reaction of 2-hydroxynaphthaldehyde with two equivalents of pyrrolidine in xylene under microwave irradiation at 170 C within 20 min, giving 2hydroxy-1-naphthylmethylamine (114) as the major product. Similarly, various aldehydes and ketones were reacted with different cyclic saturated amines producing structurally diverse mono-or di-arylmethylamines 114 in 60-74% yields (Scheme 72).…”
Section: Synthesis and Synthetic Applications Of Betti Base Derivativesmentioning
confidence: 99%
“…All derivatives showed in vivo and in vitro anti-inammatory and anthelmintic activities against reference drugs diclofenac and albendazole. 80 Jana et al 81 reported the reaction of 2-hydroxynaphthaldehyde with two equivalents of pyrrolidine in xylene under microwave irradiation at 170 C within 20 min, giving 2hydroxy-1-naphthylmethylamine (114) as the major product. Similarly, various aldehydes and ketones were reacted with different cyclic saturated amines producing structurally diverse mono-or di-arylmethylamines 114 in 60-74% yields (Scheme 72).…”
Section: Synthesis and Synthetic Applications Of Betti Base Derivativesmentioning
confidence: 99%
“…It is interesting to compare the kinetic and thermodynamic control of the reaction pathways through the carbocation intermediates (Scheme ). We suggest that iminium ions would be formed from condensation of indoline and ketone, and that these intermediates subsequently could be regenerated in the carbocation intermediates . The driving force for this process is the stabilization of these carbocation intermediates.…”
Section: Resultsmentioning
confidence: 94%
“…Unfortunately, existing N,O‐acetal generation strategies involving the trapping of oxygen by the iminium cation are better suited to the addition of phenolic oxygens via Cu(OAc) 2 , Ag 2 O or I 2 /H 2 O 2 mediated oxidations (Scheme a), or reactions of aryl aldehydes/aryl alkyl ketones with amines under metal and oxidant free conditions (Scheme b) . The limited examples involving nonphenolic hydroxyl groups include the electro‐oxidative cyclization or Ir(ppy) 2 (dtb‐bpy)PF 6 catalyzed photooxidation of hydroquinoyl and hydroisoquinoyl alcohols (Scheme c),[4b], [4c] and FeCl 3 or CHDFe(CO) 3 mediated oxidations of saturated amino alcohols (Scheme d).…”
Section: Methodsmentioning
confidence: 99%